Patients' and Practitioners' Views of Knee Osteoarthritis and Its Management: A Qualitative Interview Study - Alami, Sophie; Boutron, Isabelle; Desjeux, Dominique; Hirschhorn, Monique; Meric, Gwendoline; Rannou, François; Poiraudeau, Serge (PLOS ONE, 2011)
Purpose To identify the views of patients and care providers regarding the management of knee osteoarthritis (OA) and to reveal potential obstacles to improving health care strategies. Methods We performed a qualitative study based on semi-structured interviews of a stratified sample of 81 patients (59 women) and 29 practitioners (8 women, 11 general practitioners [GPs], 6 rheumatologists, 4 orthopedic surgeons, and 8 [4 GPs] delivering alternative medicine). Results Two main domains of patient views were identified: one about the patient–physician relationship and the other about treatments. Patients feel that their complaints are not taken seriously. They also feel that practitioners act as technicians, paying more attention to the knee than to the individual, and they consider that not enough time is spent on information and counseling. They have negative perceptions of drugs and a feeling of medical uncertainty about OA, which leads to less compliance with treatment and a switch to alternative medicine. Patients believe that knee OA is an inevitable illness associated with age, that not much can be done to modify its evolution, that treatments are of little help, and that practitioners have not much to propose. They express unrealistic fears about the impact of knee OA on daily and social life. Practitioners' views differ from those of patients. Physicians emphasize the difficulty in elaborating treatment strategies and the need for a tool to help in treatment choice. Conclusions This qualitative study suggests several ways to improve the patient–practitioner relationship and the efficacy of treatment strategies, by increasing their acceptability and compliance. Providing adapted and formalized information to patients, adopting more global assessment and therapeutic approaches, and dealing more accurately with patients' paradoxal representation of drug therapy are main factors of improvement that should be addressed.